SUDUT PENYEBARAN BEBAN PONDASI DANGKAL DI ATAS TANAH URUG - Sugie Prawono (Civil Engineering Dimension, 1999)
Existing theories of stress distribution in a homogeneous soil do not consider the effect of soil density, even though the density test is always used to check the quality of compacted fill. It is always assumed that a surface load is distributed in the soil beneath the foundation through an angle of distribution from the vertical direction. The purpose of this research is to check the relationship of the density and thickness of a filling material to the angle of distribution. Results of this investigation concluded that the angle of distribution will increase if the compacted soil was made more compact in a reduced thickness. Effect of soil density is more dominant compared to the thickness of the fill Abstract in Bahasa Indonesia : Teori distribusi tegangan dalam tanah yang homogen tidak memperhitungkan pengaruh kepadatan tanah, sedangkan metode perbaikan tanah dengan urugan justru mengandalkan kepadatan tanah urugan ini. Distribusi tegangan dalam tanah dapat dianggap sebagai hasil penyebaran beban melalui suatu sudut penyebaran tertentu, yang diukur terhadap sumbu vertikal. Penelitian ini bertujuan untuk mengetahui hubungan kepadatan dan tebal suatu tanah urug dengan sudut penyebaran tersebut. Hasil penelitian menyimpulkan bahwa sudut penyebaran (a) makin besar bilamana kepadatan tanah urug (gdry) ditingkatkan dan tebalnya dikurangi. Pengaruh kepadatan terhadap sudut penyebaran lebih dominan daripada ketebalan